Le feuillet.com. (Bruxelles : Le kiosque du gay déLIRE, 2001)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks
Redactie : Le kiosque du gay déLIRE, 13 rue Saint Jean, 1000 Bruxelles
Frans
Periodiek